Comparative Study: Traditional Agriculture vs Modern Agriculture in the Context of Sustainable Development - Kamakaula, Yohanes; Uria, Darmawanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the comparison between traditional and modern agriculture in achieving sustainable development. Traditional agriculture emphasizes local knowledge and ecosystem-friendly practices, such as crop rotation and organic fertilizers, but faces challenges in production capacity and climate resilience. Modern agriculture leverages high technology like genetic engineering and chemical inputs to enhance productivity but risks environmental degradation and economic instability for farmers. This research highlights the potential of integrating both systems through agroecology, combining traditional techniques with modern innovations. This integration can increase productivity while preserving environmental sustainability, contributing to a more balanced and sustainable agricultural system